PERANCANGAN REBRANDING NARWASTU AROMATHERAPY & BODY CARE SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Hasyl, Dinda Masfufah; Fianto, Achmad Yanu Alif; Karsam, Karsam (Jurnal ArtNouveau, 2014)
Currently there are many cosmetic industries that manufacture various kinds of body care products, one of them is Narwastu Aromatherapy & Body Care. Narwastu Aromatherapy & Body Care is an Indonesian original product that has spread almost all over Indonesia. Nevertheless, this product is still less known by the public. Therefore rebranding must done in Narwastu Aromatherapy & Body Care. The research method used is a qualitative method by interview, observation, documentation, and literature study for get the data that used to support the rebranding design drafting. From analysis of the data on designing this rebranding was found âNatural Elegantâ keyword. As well as on designing media using the Rustic concept which have the simplicity impression, natural, classic, warm, simple, clean, elegant, and modern. The results of design this rebranding is to introduce Narwastu Aromatherapy & Body Care products for more known by the public.